x-(-6-9x)+50=56

Simple and best practice solution for x-(-6-9x)+50=56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(-6-9x)+50=56 equation:


Simplifying
x + -1(-6 + -9x) + 50 = 56
x + (-6 * -1 + -9x * -1) + 50 = 56
x + (6 + 9x) + 50 = 56

Reorder the terms:
6 + 50 + x + 9x = 56

Combine like terms: 6 + 50 = 56
56 + x + 9x = 56

Combine like terms: x + 9x = 10x
56 + 10x = 56

Add '-56' to each side of the equation.
56 + -56 + 10x = 56 + -56

Combine like terms: 56 + -56 = 0
0 + 10x = 56 + -56
10x = 56 + -56

Combine like terms: 56 + -56 = 0
10x = 0

Solving
10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '10'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| 4X+2=5x+1 | | 27x^2-29x=0 | | 8s-5=9+s | | 3z+6=9 | | 5n+-3=32 | | x+3=13-19x | | -3+5n=32 | | -9w+5=-4 | | 2x^2-162=0 | | 8z+10=5 | | 6x-1=2x+23 | | 32-5k=3v+8 | | 72x^2+72x=0 | | x=(0.250+x)*(0.250+x) | | 6k-26=8k | | 14+y=17 | | 3x+7y=84 | | (2x-5)(x+4)=0 | | 5p-10=25 | | 20-4j=j | | 3xy^2+y^3=8 | | 7x+5=-9 | | 7x-8=6x+11 | | 2x+4*3x= | | 2a-8+5a=20 | | 27x-16-6x=14+21x-30 | | x^2+4x-84=0 | | 0.5x-3=2.2-0.75x | | 3y+14+(2y-7)=7y+(19-4y) | | (-5)-(4)= | | 171-4x=32x+19 | | 0.4x^2=2x^2-8.6 |

Equations solver categories